Development Strategy for Organic Fertilizers in Farmers Groups Banyuwangi Indonesia - Wahyono, Nanang Dwi; Kustiari, Tanti; Hasanah, Niswatin (Universitas Halu Oleo, 2022)
The purpose of this study was to determine the factors that influence the strategy and development of the use of organic fertilizers in Banyuwangi Regency to make the land healthier. This research was conducted in April-June 2021 in Banyuwangi Regency. The population in this study came from 5 farmer groups in Banyuwangi Regency, amounting to 350 people. The data used in the form of primary and secondary data. Primary data was obtained from the distribution of questionnaires, while the secondary data sources were obtained from the Agriculture and Food Service of Banyuwangi Regency The data obtained were analyzed using AHP (Analytical Hierarchy Process) and CSI (Customer Satisfaction Index). The results of this study indicate that 1) The priority of the strategy for developing organic fertilizer in the Banyuwangi Regency is the role of the government in supporting all activities related to organic fertilizer. 2) Farmers are satisfied with the current performance of the Banyuwangi Regency Agriculture and Food Service with a satisfaction value of 80.79%.